Recent advances in single particle rotational tracking of plasmonic anisotropic gold nanoparticles under far-field optical microscopy. Issue 7 (8th August 2016) - Ha, Ji Won
ABSTRACT: The real-time tracking of rotational motions of biological molecules in live cells is of great importance for fundamental and mechanistic studies in biological systems. Recently, plasmonic anisotropic gold nanorods (AuNRs) have attracted a great deal of attention as optical orientation probes in live-cell imaging due to their unique size- and shape-induced optical properties, photostability, large scattering and absorption cross-sections, biocompatibility, and easy surface modi-fication. Furthermore, single particle rotational tracking techniques have seen rapid development in the past 10 years. In this article, we provide a brief introduction to various far-field optical imaging and spectroscopic techniques that can be used for visualizing plasmonic Au nanoparticles. We further discuss recent developments of single particle rotational tracking techniques in combination with the AuNR probes under far-field optical microscopy.